Long term growth perspectives in Japan and the euro area - Christian Dreger (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Euro area countries and Japan are confronted with similar challenges. Potential output is on a falling trend in the euro area, and the decrease started well before the financial crisis. In Japan, low output growth is a striking feature since many years, despite the unconventional monetary policy stance and massive fiscal stimulus programs provided by the government. According to a growth accounting exercise based on a Cobb-Douglas production function, the development in both economies can be traced to a weak evolution of TFP. Weak capital deepening is detected especially in the euro area. Driven by high uncertainty with regard to the business cycle, the willingness of firms to undertake investment is only modest and constitutes the achilles heel for a smooth recovery. Both economies are not well prepared to manage the demographic challenges caused by an elderly population. Given that debt-to-GDP ratios are already at record heights, the scope for further demand driven policies is rather limited, especially in Japan. Instead, structural reforms are on the agenda to promote long run growth and a smooth development of the global economy.
Keywords: O40; E60; J11; 330; long run growth; government debt; aging population